Pengaruh Utang Domestik dan Utang Luar Negeri terhadap Pertumbuhan Ekonomi Indonesia: Periode 2004-2023 - Kasnelly, Sri; Luthfi, H. Ahmad; Jalil, Abdul; Hidayat, Suhidra; Tamsila, Ulfa (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the effect of domestic debt and external debt on Indonesia’s economic growth during the period 2004–2023. The research employs a quantitative explanatory approach using the multiple linear regression method (OLS). The results indicate that domestic debt has a significant negative effect on economic growth, while external debt has a significant positive effect. These findings suggest that an increase in domestic debt may suppress economic growth through the crowding-out effect, whereas external debt can foster economic growth when allocated to productive sectors. This study underscores the importance of a balanced debt management strategy to support sustainable development.